Effectiveness of expert semantic knowledge as a navigational aid within hypertext - Patel, Swapnesh C.; Drury, Colin C.; Shalin, Valerie L. (Behaviour & information technology, 1998)
Hypertext systems parse documents into content nodes connected by machine supported links or relationships. Many hypertext researchers claim that the node-link relationships of hypertext provide an information organization that models the structure of human knowledge and should therefore facilitate information access (Fiderio 1988). Yet, failures of information access occur when users lack an understanding of the overall scope and organization of a hypertext system (Gay and Mazur 1991). To support this understanding, the present research incorporated expert-based domain semantics in the design of prosthetic devices for hypertext navigation. The task domain was documentation for a word processing system. In the first experiment, the pathfinder algorithm (Schvaneveldt 1990) and cluster analysis were used to identify a set of expertbased semantic relationships between word-processing concepts. The results from these analyses contributed to the design of two prostheses to assist hypertext navigation: A hierarchical index and a local semantic browser. These aids were tested in a second experiment, crossing type of on-line documentation (semantically enhanced hypertext or an alphabetically indexed text) with level of subject expertise (novice or expert). Both performance and strategy measures suggest that the semantic prostheses improved the accessibility of information for novice users without hampering expert performance.